Production and characterization of non-leaching antimicrobial and hydrophilic polycaprolactone based nanofiber mats. (15th April 2021) - Aynali, Figen; Balci, Huseyin; Doganci, Erdinc; Bulus, Erdi
Graphical abstract: Highlights: Fabrication of novel antimicrobial and hydrophilic nanofiber biomaterial. Blending of synthesized PLA based ( co )polymer into PCL matrix via electrospinning. Examination of antimicrobial activity against S. aureus and E. coli bacterial. Fabrication of hydrophilic material because of having quaternary ammonium salts. Abstract: Novel antimicrobial and hydrophilic nanofiber biomaterial was fabricated with a combination of surface modification and nanotechnology, in this study. For this purpose, firstly poly(lactic acid) (PLA) bearing quaternary ammonium salt as an antimicrobial agent on its backbone in the rates of 5% by mole were successfully fabricated with a combination of ring-opening copolymerization and copper(I)-catalysed azide-–alkyne cycloaddition click reaction in a two-step reaction procedure. Then, this synthesized polymer was blended into polycaprolactone (PCL) matrix in three different proportions via electrospining technique. The prepared nanofiber mats were then characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and contact angle analysis. In addition, thermal properties of mats were examined through differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA) experiments. Its importance as an antimicrobial biomaterial was analyzed using Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) which were types of Gram-positive and Gram-negative bacteria, respectively. As a result, it was observed that as the rate of antimicrobial polymer in the nanofiber material increased, its antimicrobial activity against both bacteria also increased. As a result of the highest blending ratio of antimicrobial PLA copolymer, the bacterial population amount decreased by 99.5% and 92% for S. aureus and E. coli, respectively, as compared to neat PCL nanofiber mat. Besides, thermal properties of PCL nanofiber mats did not changed negatively after the blending process, even char yield increased slightly with increasing rate of antimicrobial PLA content. Also, the results showed that the blending of PCL nanofiber mat with antimicrobial PLA having quaternary ammonium salts on its backbone maked it highly hydrophilic.